The Root Problems of Agrarian Conflict in Plantation Sector: A Study Case in Riau Province - Mifta Hadi Safii (Budapest International Research and Critics University, 2022)
This writing aimed at discovering and retrieving the overview of agrarian conflict roots in plantation sector in Riau Province. Riau is one of the provinces which has high agrarian conflicts in plantation sector compared to other provinces in Indonesia. The root problems of agrarian conflict in plantation sector in this research are quite complex because the state has a quire huge role in stimulating the occurrence of the conflicts by formulating policies. Those several governmental policies are the administration of Business Use Rights to companies, regulation formulation such as Plasma Garden and Customary Land. The community’s claim is the implication of the regulation issued by the government. The public policies formulated by the government which become the conflict source will only be able to be signed when the government has the commitment to solve them through governmental institution and organization in related field.